CT-based quantification of short-term tissue shrinkage following hepatic microwave ablation in an in vivo porcine liver model. (January 2021) - Erxleben, Christoph; Niehues, Stefan M; Geyer, Beatrice; Poch, Franz; Bressem, Keno K; Lehmann, Kai S; Vahldiek, Janis L
Background: Microwave ablation (MWA) is a minimally invasive treatment option for solid tumors and belongs to the local ablative therapeutic techniques, based on thermal tissue coagulation. So far there are mainly ex vivo studies that describe tissue shrinkage during MWA. Purpose: To characterize short-term volume changes of the ablated zone following hepatic MWA in an in vivo porcine liver model using contrast-enhanced computer tomography (CECT). Material and Methods: We performed multiple hepatic MWA with constant energy parameters in healthy, narcotized and laparotomized domestic pigs. The volumes of the ablated areas were calculated from venous phase CT scans, immediately after the ablation and in short-term courses of up to 2 h after MWA. Results: In total, 19 thermally ablated areas in 10 porcine livers could be analyzed (n = 6 with two volume measurements during the measurement period and n = 13 with three measurements). Both groups showed a statistically significant but heterogeneous volume reduction of up to 12% (median 6%) of the ablated zones in CECT scans during the measurement period ( P  < 0.001 [n = 13] and P  = 0.042 [n = 6]). However, the dimension and dynamics of volume changes were heterogenous both absolutely and relatively. Conclusion: We observed a significant short-term volume reduction of ablated liver tissue in vivo. This volume shrinkage must be considered in clinical practice for technically successful tumor treatment by MWA and therefore it should be further investigated in in vivo studies.